ANTIFUNGAL ACTIVITY AND ACUTE TOXICITY OF STEM BARK EXTRACTS OF DRYPETES GOSSWEILERI S. MOORE-EUPHORBIACEAE FROM CAMEROON - Ngouana, Vincent; Fokou, Patrick Valère Tsouh; Foudjo, Brice Ulrich Saha; Ngouela, Silvère Augustin; Boyom, Fabrice Fekam; Zollo, Paul Henri Amvam (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Drypetes gossweilleri S. Moore is a plant used in traditional medicine in Cameroon. The antifungal properties of its stem-bark crude extract and fractions DG1, DG2, DG3, DG4, DG5, DG6, DG7, DG8 and DG9 were assayed by agar and broth dilution methods on solid and liquid media against C. Krusei, C. albicans, C. glabrata, T. mentagerophytes, M. langeroinii, M. gypeum, M. audouini, T. rubrum, T. soudanense, T. terrestre, A. flavus and A. niger. The results revealed a substantial antifungal effect with minimal inhibitory concentrations ranging respectively from 24.11Âµg/ml to 1562Âµg/ml for yeasts and from 3125Âµg/ml to 12500Âµg/ml for filamentous fungi. Among the fractions, fraction DG4 exerted the highest antifungal activity. Moreover, no toxic effect was noticed in male and female albinos Wistar rats treated per os with the crude stem bark’s extract of Drypetes gossweileri at a dose up to 12g/kg of body weight. The phytochemical screening of the crude extract and fractions showed the presence of alkaloids, phenols, flavonoids, saponins, anthocyanines, anthraquinones, sterols, lipids and essential oils. Therefore, Drypetes gossweileri may be safe as phytomedecine for the treatment of fungal infections.